Analisis Pembangunan Knowledge Management System Pada Unit Kerja Asdep Dumas Kemensetneg RI Dengan Framework COBIT 5.0 - Novryzal, Andress; Pranoto, Edi (STMIK Banjarbaru, 2025)
The very rapid development of information technology in the era of disruption has changed various work processes, including the management of public complaints at the Ministry of State Secretariat of the Republic of Indonesia, the number of which continues to increase every year. To increase the speed and accuracy of analysis, the Assistant Deputy for Public Complaints developed a Knowledge Management System as a means of accessing and managing case references. This research evaluates the suitability of system development to organizational needs and assesses the maturity level of IT processes using a COBIT 5-based audit. The approach used is a mixed method through literature study, distributing questionnaires to 15 Dumas analysts, and interviews with relevant officials. The research results show that the maturity level is at level 4 (managed), while the organization's target is level 5. The gap value found in EDM02 was 0.9, EDM04 was 0, APO04 was 0.67, and APO12 was 0.89, indicating the need for process improvement to achieve the expected maturity level.Keywords: Cobit 5.0; Knowledge Management System; Maturity level; Dumas AbstrakPerkembangan teknologi informasi yang sangat pesat pada era disrupsi telah mengubah berbagai proses kerja, termasuk pengelolaan pengaduan masyarakat di Kementerian Sekretariat Negara RI yang jumlahnya terus meningkat setiap tahun. Untuk meningkatkan kecepatan dan ketepatan analisis, Asisten Deputi Pengaduan Masyarakat mengembangkan Knowledge Management System sebagai sarana akses dan pengelolaan referensi kasus. Penelitian ini mengevaluasi kesesuaian pengembangan sistem dengan kebutuhan organisasi serta menilai tingkat kematangan proses TI menggunakan audit berbasis COBIT 5. Pendekatan yang digunakan merupakan metode campuran melalui studi pustaka, penyebaran kuesioner kepada 15 analis dumas, dan wawancara dengan pejabat terkait. Hasil penelitian menunjukkan tingkat kematangan berada pada level 4 (managed), sementara target organisasi adalah level 5. Nilai kesenjangan yang ditemukan EDM02 sebesar 0,9, EDM04 sebesar 0, APO04 sebesar 0,67, dan APO12 sebesar 0,89 mengindikasikan perlunya peningkatan proses untuk mencapai tingkat kematangan yang diharapkan.